Validitas Modul Fisika Berbasis Model Pembelajaran Discovery Learning Pada Materi Kalor dan Termodinamika Berbantuan Live Worksheet untuk Kelas XI SMA/MA - Anggia Murni, Khairunisa; Hufri, Hufri; Mufit, Fatni; Satria Dewi, Wahyuni (CV. Creative Tugu Pena, 2024)
Modules become teaching materials that can support the implementation and characteristics of an independent curriculum. The lack of use of modules as teaching materials that help students learn independently is an obstacle in improving competence so that it has an impact on learning outcomes. A possible solution is to develop a physics module based on discovery models for class XI SMA/MA. The research aims to develop a physics module with valid criteria. This type of research uses research and development with the ADDIE design model. The research instrument used was a validation questionnaire sheet from 3 FMIPA UNP physics lecturers. The module validity results are in the very valid category with an average of 82%. This research produces a physics module based on a discovery learning model on heat and thermodynamics material with the help of live worksheets for class XI SMA/MA which is valid. Keywords: Discovery Learning, Live Worksheet, Kalor, Termodinamika